2001
DOI: 10.1074/jbc.m101890200
|View full text |Cite
|
Sign up to set email alerts
|

The Latency-associated Nuclear Antigen of Kaposi's Sarcoma-associated Herpesvirus Transactivates the Telomerase Reverse Transcriptase Promoter

Abstract: Telomerase is a multi-subunit ribonucleoprotein holoenzyme that stabilizes telomere length through the addition of new repeat sequence to the ends of chromosomes. Telomerase reverse transcriptase is the subunit of this complex responsible for the enzymatic activity of telomerase. Expression of the reverse transcriptase is regulated at the level of transcription through the action of transcription factors that target its promoter. Most Kaposi's sarcoma tumor cells are latently infected with the Kaposi's sarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 64 publications
3
111
1
Order By: Relevance
“…All reporter constructs were more strongly expressed in either line than in normal ®broblasts, and there were no signi®cant di erences between the activity of any of the reporters in the telomerase positive and the ALT line. Knight et al (2001) have also reported hTERT promoter activity in an ALT cell line SUSM-1 when using another reporter containing 1.7 kb of the hTERT¯anking region. Even more strikingly, we observed no di erences in the expression of the same hTERT reporters when we compared them in a breast carcinoma line and its derivatives in which transfer of a single normal chromosome 3 has reduced hTERT mRNA by at least 30-fold, to undetectable levels (Ducrest et al, 2001).…”
Section: On the Use Of Htert-reporter Constructsmentioning
confidence: 99%
“…All reporter constructs were more strongly expressed in either line than in normal ®broblasts, and there were no signi®cant di erences between the activity of any of the reporters in the telomerase positive and the ALT line. Knight et al (2001) have also reported hTERT promoter activity in an ALT cell line SUSM-1 when using another reporter containing 1.7 kb of the hTERT¯anking region. Even more strikingly, we observed no di erences in the expression of the same hTERT reporters when we compared them in a breast carcinoma line and its derivatives in which transfer of a single normal chromosome 3 has reduced hTERT mRNA by at least 30-fold, to undetectable levels (Ducrest et al, 2001).…”
Section: On the Use Of Htert-reporter Constructsmentioning
confidence: 99%
“…In addition to its role in viral episome maintenance, LANA modulates host cell behavior to create a suitable environment for latent KSHV persistence. LANA can cooperate with activated ras in fibroblast transformation assays (38) and activates the human telomerase promoter (39). Biochemical studies show that LANA binds to p53, Rb (38,40), and a growing number of cellular transcription factors: Ring3, mSin3, ATF/CREB2, and CREB-binding protein (41)(42)(43)(44).…”
mentioning
confidence: 99%
“…Interestingly, a number of viral oncogenic proteins such as human papillomavirus (HPV) E6 and the latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus have been shown capable of inducing telomerase activity through a direct transactivation of the hTERT gene and in turn contributing to the transformation process. 38,39 Given a potential role for LMP2A in EBVmediated tumorigenesis, we hypothesized a link between LMP2A and telomerase or hTERT regulation. To our surprise, LMP2A showed a significant inhibition of telomerase and hTERT expression, pointing to the diverse influence of tumor-viral proteins on telomerase/hTERT regulation.…”
mentioning
confidence: 99%